1984
DOI: 10.1111/j.1365-3083.1984.tb00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of the Terminal C5b‐9 Complex of Human Complement by a Sensitive Enzyme‐Linked Immunosorbent Assay

Abstract: An enzyme-linked immunosorbent assay for detection and quantification of the terminal complexes (SC5b-9 and membrane attack complex) of human complement is described. We separate the complex from the native complement components, to use antibodies against the native components in a 'double-antibody sandwich' technique. It is thereby possible to detect the terminal complement complex in solution without the requirement of specific antibodies against the neoantigens. The results show that the assay is both sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…However, whereas demonstration MAC and contains the S-protein [12] in addi tion to the terminal components. Recently, the fluid-phase TCC has been described in normal human plasma [13] and in increased amounts in patients with activation of com plement in vivo [14], We have observed that some patients have increased plasma levels of both C3d,g and TCC, whereas in others only one of these is increased. In addition, it was observed that C3d,g seemed to increase more rapidly than TCC during storage.…”
Section: Introductionmentioning
confidence: 75%
“…However, whereas demonstration MAC and contains the S-protein [12] in addi tion to the terminal components. Recently, the fluid-phase TCC has been described in normal human plasma [13] and in increased amounts in patients with activation of com plement in vivo [14], We have observed that some patients have increased plasma levels of both C3d,g and TCC, whereas in others only one of these is increased. In addition, it was observed that C3d,g seemed to increase more rapidly than TCC during storage.…”
Section: Introductionmentioning
confidence: 75%
“…This assay is based on a monoclonal antibody (aE11) highly specific for a neoepitope exposed in C9 when incorporated into TCC [14,15]. Values are given in arbitrary units (AU) according to a serum standard activated with zymosan, defined to contain 1,000 AU/ml.…”
Section: Methodsmentioning
confidence: 99%
“…This complex known as SC5b-9, where S stands for S protein or vitronectin, is detected in the circulation and in the extravascular fluid and is commonly regarded as an irrelevant byproduct of C activation (12), although a possible effect of SC5b-9 was postulated by Ishikawa et al (13) in pulmonary hydraulic conductivity. We have previously shown that a cytolytically inactive complex (iTCC), prepared by incubating purified late components and differing from SC5b-9 for the lack of vitronectin and clusterin, despite the inability to lyse target cells, was still able to bind to endothelial cells and to stimulate these cells to express adhesion molecules and tissue factor (14).…”
mentioning
confidence: 99%